Chapter 4 Godofredo and Françoise Travel Around the World Phantoms, Radioiodine Uptake Tests, and the IAEA's Standardization Projects - Rentetzi , Maria (Taylor & Francis, 2024)
This chapter focuses on Françoise, a dummy figure of the upper part of the female human body used for calibrating radiation detectors in laboratories around the world. From spring 1962 to the end of 1965, Godofredo Gómez Crespo, a Spanish physicist employed by the International Atomic Energy Agency, travelled the world carrying Françoise in a box-like suitcase that also included a number of standard vessels of various sizes and shapes, containing amounts of mock radioiodine. Gómez Crespo's task was to check the precision of radioiodine uptake tests for quality assurance in in-vivo measurements in several hospital laboratories across the globe. At the time, thyroid uptake tests constituted one of the first diagnostic applications of radioactive tracers, a cutting-edge technique in nuclear medicine. The chapter discusses the unnecessary gendering of physics instrumentation and brings front and centre the legacy of sexism in the nuclear sciences.